Production of butyric acid by the cellulolytic actinobacterium Thermobifida fusca - Merklein, Kyle (Kansas State University, 2015)
Thermobifida fusca, an aerobic moderately thermophilic, filamentous soil bacterium is capable of producing butyric acid. Butyric acid is a 4-carbon short chain fatty acid that is widely used in the chemical, food, and pharmaceutical industries. Currently, butyric acid is primarily produced through petroleum-based chemical synthesis, but could be a candidate to be produced by fermentation. By producing through a fermentation platform, production of butyric acid can be shifted from a non-renewable to a renewable source. In an effort to make T. fusca produce a high yield of butyric acid, multiple fermentation parameters were explored and optimized. The effect of different carbon sources (mannose, xylose, lactose, cellobiose, glucose, sucrose, and acetates) on butyric acid production was studied, where cellobiose produced the highest yield of 0.67 g/g C (g-butyric acid/g-carbon input). The best stir speed and aeration rate for butyric acid production were found to be 400 rpm and 2 vvm in a 5-L fermentor. The maximum titer of 2.1 g/L butyric acid was achieved on 9.66 g/L cellulose. Fermentation was performed on ground corn stover as a substrate to evaluate the production of butyric acid on lignocellulosic biomass, and the optimized conditions resulted in a titer of 2.37 g/L butyric acid. The butyric acid synthesis pathway was identified involving five genes that catalyzed reactions from acetyl-CoA to butanyol-CoA in T. fusca. A study into the transcriptomics of T. fusca was begun by growing T. fusca under a variety of fermentation conditions, isolating the messenger RNA, and performing a sequence of the mRNA using whole transcriptome shotgun sequencing. The results of sequencing of various samples were plotted to determine correlation across numerous fermentation parameters. This correlation based analysis determined that the carbon to nitrogen ratio has the largest overall impact on gene transcription of T. fusca among all of the fermentation parameters studied. Overall, the work from this study proves that production of butyric acid is possible from a renewable cellulosic feedstock.
Keywords: butyric acid; biomass; Consolidated Bioprocessing; Biochemistry (0487); Engineering, Agricultural (0539)